Correlation between integrin alpha 5 expression and the malignant phenotype of transitional cell carcinoma. - Saito, T. (Nature Publishing Group, 1996)
We examined the expression of alpha 1, alpha 2, alpha 3, alpha 4, alpha 5 and beta 1 integrin on 36 transitional cell cancers (TCCs) in the bladder by immunohistochemistry. Only alpha 2, alpha 3 and beta 1 were detected on normal transitional cell epithelium, but four TCCs (12.5%) revealed positive staining for alpha 1, seven (19.4%) for alpha 4 and seven (20%) for alpha 5. These altered expressions of integrin alpha chain were more frequent in histologically higher stage or grade of TCC, and a correlation was found between increased alpha 5 expression and histological stage. alpha 5 was positive in 6 (35.3%) of 17 invasive TCCs whereas only 1 (5.9%) of 17 superficial TCCs. Flow cytometric analysis on bladder cancer cell lines showed that T24 and HT1376, which are undifferentiated TCC cell lines, highly expressed alpha 5 and beta 1. Also, SCaBER, which is derived from urinary bladder squamous cell cancer and which is recognised as the most malignant phenotype after metaplasia of transitional epithelium, had alpha 5 and beta 1. However, RT4, which is derived from transitional cell papilloma, showed no expression of alpha 5. Furthermore, reverse transcriptase-polymerase chain reaction (RT-PCR) showed the presence of mRNA of alpha 5 on T24, SCaBER and HT1376, but not on RT4. Taken together, it seems that the presence of alpha 5 integrin might be a more malignant phenotype in transitional cell carcinoma. IMAGES: